ANALISIS PELAKSANAAN PENGELOLAAN SANITASI LAUNDRY (LINEN) DI RUMAH SAKIT UMUM MARTHA FRISKA MEDAN TAHUN 2014 - Suriani Gultom; indra chahaya; taufik ashar (Lingkungan dan Kesehatan Kerja, 2014)
Sanitation management of the linen is one special sanitation efforts at the hospital because it has sharp attention on the activities or processes because of its distinctive properties and can cause hazard/risk high for officers, hospital visitors and patients. Many of the problems that will probably arise from nosocomial infections, among others, when health workers who suffer from infections due to certain pathogenic microorganisms, it is because the health care personnel with direct patient contact, because linen is the object that engaged directly with patients and the management of the linen is not good will give negative impact to the hospital The present study is a descriptive survey with the object includes the operation of sanitation linen of Martha Friska Hospital Medan and 10persons of loundry as the respondent by using direct observation for the object of the study and direct interview with the informant. The objective of the study is to know the facility and infrastructure of laundry sanitation, characteristics (age, duration of service on job, education level, participation in training and knowledge) and analysis of the solid waste treatment of Martha Friska hospital Medan in 2014. The result of the study showed that the score of all variables is of 70%. It indicates that in fact, the operation of laundry sanitation of Martha Friska hospital Medan was still not adjusted to the requirements of laundry sanitation according to Kepmenkes RI with the minimal standard of ≥ 80%. The conclusion of the study is that the operation of the solid waste treatment of hospital is still not adjusted to the Kepmenkes RI , including the inadequate facility and infrastructure. For that reason, it is expected that all the laundry installation of Martha Friska hospital to more increase in the supportive facility by supplying the more complete facility and infrastructure to the laundry that they use the complete self-protective tool Keywords: Analysis, Operation, Treatment, Sanitation, loundry